Types and Abundance of Phytoplankton in Tanjung Kudu Lake and Parit Lake, Tambang District, Kampar Regency, Riau Province - Rekha Mutiara Manurung; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTPhytoplankton is primary producer and as well as natural food and has an important role in the water. This research was conducted in December 2020 in Tanjung Kudu Lake and Parit Lake. There were three stations, namely Station 1 (inlet), Station 2 (in the middle of the lake), and Station 3 (end of the lake). Sampling was done 3 times one/week. Water quality parameters measure were temperature, transparency, depth, pH, dissolved oxygen, CO2, nitrate, and phosphate. Result shown there were 26 types of phytoplankton in Tanjung Kudu Lake, and 29 species in Parit Lake. The abundance of phytoplankton in Lake Tanjung Kudu was 18,720-37,700 cells/L, and the abundance of phytoplankton in Lake Parit was 19,760-45,500 cells/L. Water quality parameter such as transparency 48.5-59 cm, temperature 29.3-29.6oC, pH 5.3-5.8, dissolved oxygen 3.42-4.57 mg/L, CO2 11.98-13.98 mg/L, nitrate 0.035-0.038 mg/L and phosphate 0.027-0.048 mg/L in Lake Tanjung Kudu where as in Lake Parit the transparency was 59-65.67 cm, temperature 29.3-9.8oC, pH 5-6, dissolved oxygen 4.19-5.18 mg/L, CO2 10.66-13.32 mg/L, nitrate 0.03-0.04 mg/L and phosphate 0.036-0.039 mg/L. Based on the abundance of phytoplankton, Lake Tanjung Kudu and Lake Parit can be categorized as mesotrophic.Keywords: Phytoplankton, Water Quality Parameters, Tanjung Kudu Lake, Parit Lake, Mesotrophic